Formulasi dan evaluasi ekstrak daun wuru ketek dalam pasta gigi sebagai anti bakteri - Cedric, Alif; Adrianto, Dimas; Arianti, Varda; Fakriah, Amalina (Indonesian Journal of Health Science, 2025)
The wuru ketek plant (shrub/small tree) contains antibacterial substances, making it a potential alternative for toothpaste formulation. Toothpaste functions as a cleaning cosmetic, mouth freshener, and caries prevention. Caries itself is caused by demineralization of the tooth surface due to bacterial growth, one of which is Staphylococcus aureus. This study focuses on the effectiveness of wuru ketek leaf extract in toothpaste formulation. The results of the antibacterial test showed varying inhibition zones: formula 1 was 10.25 mm, formula 2 was 17.25 mm, and formula 3 was 14.20 mm. In addition, physical evaluation of toothpaste (including organoleptic, homogeneity, spreadability, pH, foam height, and viscosity) was carried out through accelerated stability tests at extreme temperatures, room, and controlled for 45 days. All physical parameters of the preparation have met the requirements. Tanaman wuru ketek (perdu/pohon kecil) mengandung zat antibakteri, menjadikannya alternatif potensial untuk formulasi pasta gigi. Pasta gigi berfungsi sebagai kosmetik pembersih, penyegar mulut, dan pencegah karies gigi. Karies gigi sendiri disebabkan oleh demineralisasi permukaan gigi akibat pertumbuhan bakteri, salah satunya Staphylococcus aureus. Penelitian ini berfokus pada efektivitas ekstrak daun wuru ketek dalam formulasi pasta gigi. Hasil uji antibakteri menunjukkan zona hambat yang bervariasi: formula 1 sebesar 10,25 mm, formula 2 sebesar 17,25 mm, dan formula 3 sebesar 14,20 mm. Selain itu, evaluasi fisik pasta gigi meliputi (organoleptis, homogenitas, daya sebar, pH, tinggi busa, dan viskositas) dilakukan melalui uji stabilitas dipercepat pada suhu ekstrem, ruang, dan terkontrol selama 45 hari. Semua parameter fisik sediaan tersebut telah memenuhi persyaratan.